Study of viscous-britle fractures of experimental pipes of different manufacturing technologies during natural tests - MAKARENKO, Valeriy; GOTS, Volodymyr; BERDNYK, Oksana; AMELINA, Nataliya; MAISTRENKO, Alla (Ways to Improve Construction Efficiency, 2024)
A method based on the principles of acoustic emission has been developed and tested to determine the rate of crack propagation in pipes during field (full-scale) tests while comparing the results obtained on full-thickness DWTT samples. The mechanism of viscous-brittle fracture of pipes of different strength and viscosity classes was established. The principles of increasing the resistance of pipe metal to fracture are determined. The steels of controlled rolling and progressive heat treatment with the use of accelerated (spray) cooling were studied. Recommendations for extending the operational (trouble-free) life of long-duration gas pipelines are given. It is known that as the elastic energy reserve increases, the working conditions of the metal in the structure become more difficult, the fracture resistance decreases, and the critical crack length capable of spontaneous development and the stress intensity factor decrease. At the moment of crack formation in the pipe metal, the stored elastic energy is almost instantly transferred to the fracture zone and contributes to its propagation. In addition, in addition to the energy stored by the compressed gas, the energy of elastic deformation of the metal is also stored in the pipeline. Such elastic energy stored in the pipe metal is determined by the combined effects of annular and longitudinal stresses according to the formula E = 5/32 (p2 D2 S)/Eh, where p – pressure in the pipe; D – pipe diameter; S – pipe surface; h – pipe wall thickness; E – modulus of elasticity of the metal. The above formula shows that the value of the elastic deformation energy stored by the metal is determined by the operating parameters of the pipeline. For example, for a gas pipeline with a diameter of 1420 mm and a working pressure of 7,5 MPa, the specific elastic energy in a 14 mm thick pipe wall is 2 MJm2 , and for a pipeline with a diameter of 1020 mm with the same wall thickness and a working pressure of 5,5 MPa – only 0,4 MJm2 . It should be noted that an increase in the elastic energy of the metal in the structure contributes to the localization of the deformation in the defect and its accelerated development. In main pipelines, where a wide range of steels is used and there is a high probability of concentrators, an increased elastic energy reserve contributes to a decrease in metal performance. Therefore, it is necessary to clearly understand the mechanism of influence of the elastic energy reserve in the pipeline metal on its performance. The negative impact of the energy stored in the metal of the pipe on the operation of gas and oil pipelines is manifested in their numerous destructions with severe economic and environmental consequences, which encourages scientists to further study this problem.